Observations on occurrence of poultry diseases associated with mycotoxins in feed - JAND, S K; SINGH, P P; SINGH, AMARJIT (The Indian Journal of Animal Sciences, 2013)
A survey was conducted to find out the prevalence of poultry diseases associated with mycotoxins in feed i.e. secondary mycotoxin diseases at different poultry farms (65) having a popUlation of 24 1320 birds. Mycotoxins were precent at 29 (78.3%) and 23 (82.1 %) broiler and layer farms respectively. Secondary mycotoxin diseases were observed at 18 (62%) of 29 broiler farms, whereas, 22 (95.60/0) of the 23 iayer farms were having secondary mycotoxin diseases. Inclusion body hepatitis (IBH) was the most common secondary mycotoxin infection present at the broiler fanns. whereas decrease in egg production was the predominant disease condition at the layer farms. The other concurrent conditions/ infections at the poultry farms were, infectious bursal disease (IBD). Ranikhet disease, air sacculitis, salmone/losis. coccidiosis. rickets, avitaminosis and respiratory problems. Different types of mycotoxins detected from the poultry feeds at these farms in decreasing order of frequency were aflatoxins, ochratoxins. citrinin and sterigmatocystine, either found singly or in combination.